Loyalty intentions. Issue 3 (12th August 2014) - Mathew, Veeva; Thirunelvelikaran Mohammed Ali, Rofin; Thomas, Sam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This article aims to present a model linking loyalty intention, brand commitment, brand credibility and brand awareness. The model shows the mediating role of brand commitment and brand credibility on loyalty intention. The researchers also investigated the changes in the given model under high and low involvement conditions, explicitly considering involvement as between-subject differences rather than between-product differences. The change in customer loyalty intention under varying levels of product involvement is a highly debated topic among researchers. Design/methodology/approach – The model was tested on a sample of 318 executives who have bought and are using deodorants. The respondents had given responses for loyalty intentions, brand commitment, brand credibility, brand awareness and involvement towards the brand of deodorant that they use. Confirmatory factor analysis was used to validate the tool for measurement of constructs and multi-group structural equation modelling for testing the hypotheses and comparing the nested models. Findings – The difference between high and low involvement groups in the given model supports the hierarchy-of-effects view. We found that attitude precedes behaviour for highly involved individuals but followed a different hierarchy among the individuals with low involvement. Research limitations/implications – This research investigates the proposed model for a single product category and so the scope of generalisability is limited to the product selected. This research has considered behavioural intention rather than the behaviour in this study. Practical implications – The study demonstrates the differences in the hierarchy-of-effects among low/high involvement groups. Thus, the findings will have an impact on the approach of practitioners, as different strategies will have to be adopted for the enhancement of loyalty intentions based on the difference in perceived involvement of consumers. Originality/value – This paper shows the need to differently target consumers with different levels of perceived involvement, within the same product class and thus between-subject involvement can be used as a segmentation variable.